Mitigating the Challenges of Small and Medium Enterprises in Nigeria - Babandi Ibrahim Gumel (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- The purpose of the paper is to provide owners and managers of small businesses with necessary information about the challenges facing small businesses in Nigeria and present the possible tools, policies, and strategies to mitigate them. Design/Methodology- Using the multi-case qualitative study, managers of successful small businesses narrated in an interview the tools, policies, and strategies they used to mitigate the identified challenges. The study answered the central question: what are the tools, policies, and strategies used by managers of successful small businesses to mitigate the challenges facing their firms? Findings- The findings identified continuous government intervention and support to small businesses as a major tool that reduced the challenges facing the sector. Practical Implications- The information found in this study can be used by small business managers to mitigate the challenges facing small businesses and reduce their massive failure in the economy. Mitigating the challenges facing small businesses in Nigeria will increase the number of successful small businesses, which will result in the reduced unemployment rate in the economy. A reduced unemployment rate in the Nigerian economy will increase the wellbeing of citizens, thereby reducing the unemployment rate in the economy.